2018
DOI: 10.1136/jnnp-2018-317947
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid immunoglobulin light chain ratios predict disease progression in multiple sclerosis

Abstract: ObjectiveTo determine whether the ratio of cerebrospinal fluid (CSF) immunoglobulin kappa to lambda light chains at time of multiple sclerosis (MS) diagnosis predicts disease progression and whether this was intrinsic to CSF plasmablasts.MethodsCSF and peripheral blood were obtained from patients undergoing elective diagnostic lumbar puncture and included clinically isolated syndrome (CIS) (n=43), relapsing remitting MS (RRMS; n=50), primary progressive MS (PPMS; n=20) and other neurological disease controls, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 36 publications
3
35
0
3
Order By: Relevance
“…CSF cells, on the other hand, provide a way to directly study immunology in the central nervous system. Indeed, recent studies of intrathecal immunity by us and others have shown this understudied immune compartment to be relevant to the pathobiology of neurodegenerative diseases (3,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Yet CSF cells have been widely understudied because of the invasive method of CSF extraction (typically lumbar puncture), and because cells are often discarded for proteomic analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CSF cells, on the other hand, provide a way to directly study immunology in the central nervous system. Indeed, recent studies of intrathecal immunity by us and others have shown this understudied immune compartment to be relevant to the pathobiology of neurodegenerative diseases (3,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Yet CSF cells have been widely understudied because of the invasive method of CSF extraction (typically lumbar puncture), and because cells are often discarded for proteomic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only the multiple sclerosis field has rigorously evaluated live CSF cells (3,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), with sparse investigations in the context of AD (15,16), narcolepsy (17), Rasmussen encephalitis (18), and paraneoplastic cerebellar degeneration (19). Lueg et al report increased activation of CD4 + and CD8 + T cells in patients with AD and mild cognitive impairment (MCI) (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the journal, Rathbone et al 1 provide further evidence to support the utility of the ratio of cerebrospinal fluid (CSF) immunoglobulin kappa to lambda free light chains (FLC κ:λ ratio), measured at diagnostic lumbar puncture (LP) at the time of CIS, in predicting multiple sclerosis (MS) disease progression out to 5 years post-CIS.…”
Section: There Is a Critical Need For A Prognostic Biomarker At The Tmentioning
confidence: 99%
“…Tento test je používán vzácně vzhledem ke své větší pracnosti, zejména ve srovnání s novými automatizovanými kvantitativními metodami. U RS byla popsána také intratékální syntéza fLC typu lambda (free lambda light chains; fLLC) a přestože je nacházena vzácněji než intratékální syntéza IgG a fKLC [5, 7,8], recentní studie ukazují, že současná analýza fKLC a fLLC může mít prognostický význam [9][10][11].…”
unclassified